Effect of Acute Hypoxia on Post-Exercise Parasympathetic Reactivation in Healthy Men - Al Haddad, Hani; Mendez-Villanueva, Alberto; Bourdon, Pitre C.; Buchheit, Martin (Frontiers in Physiology, 2012)
In this study we assessed the effect of acute hypoxia on post-exercise parasympathetic reactivation inferred from heart rate (HR) recovery (HRR) and HR variability (HRV) indices. Ten healthy males participated in this study. Following 10 min of seated rest, participants performed 5 min of submaximal running at the speed associated with the first ventilatory threshold (Sub) followed by a 20-s all-out supramaximal sprint (Supra). Both the Sub and Supra runs were immediately followed by 15 min of seated passive recovery. The resting and exercise sequence were performed in both normoxia (N) and normobaric hypoxia (H) (FiO2 = 15.4%). HRR indices (e.g., heart beats recovered in the first minute after exercise cessation, HRR60s) and vagal-related HRV indices (i.e., natural logarithm of the square root of the mean of the sum of the squared differences between adjacent normal R-R intervals (Ln rMSSD)) were calculated for both conditions. Difference in the changes between N and H for all HR-derived indices were also calculated for both Sub and Supra. HRR60s was greater in N compared with H following Sub only (60±14 vs. 52±19 beats.min-1, P = 0.016). Ln rMSSD was greater in N compared with H (post Sub: 3.60±0.45 vs. 3.28±0.44 ms in N and H, respectively and post Supra: 2.66±0.54 vs. 2.65±0.63 ms, main condition effect P = 0.02). When comparing the difference in the changes, hypoxia decreased HRR60s (-14.3%±17.2 vs. 5.2-0.5%±19.3; following Sub and Supra, respectively; P = 0.03) and Ln rMSSD (-8.6%±7.0 vs. 2.0%±13.3, following Sub and Supra, respectively; P = 0.08, Cohen’s effect size = 0.62) more following Sub than Supra. While hypoxia may delay parasympathetic reactivation following submaximal exercise, its effect is not apparent following supramaximal exercise. This may suggest that the effect of blood O2 partial pressure on parasympathetic reactivation is limited under heightened sympathetic activation.